The effects of circularly polarized light on mating behavior and gene expression in Anomala corpulenta (Coleoptera: Scarabaeidae) - Li, Tong; Jiang, Yueli; Yang, Xiaofan; Li, Huiling; Gong, Zhongjun; Qin, Yifan; Zhang, Jing; Lu, Ruijie; Wei, Guoshu; Wu, Yuqing; Lu, Chuantao (Frontiers in Physiology, 2023)
Light is among the important abiotic factors affecting insect linear polarized light is common in nature, circularly polarized light is rare. Left circularly polarized light (LCP) is selectively reflected by the exocuticle of most scarab beetles, including Anomala corpulenta. Despite our previous research showing that this visual signal probably mediated their mating behavior, how it affects the mating of A. corpulenta is not well elucidated. In this study, we deciphered how LCP affects not only their mating behavior but also their gene expression using RNA-seq. The results indicated that disturbed LCP reflection in A. corpulenta females probably affected the mate searching of the males. This showed that LCP probably could be perceived by A. corpulenta males, which further mediated their mating behavior. However, this hypothesis needs future verification with more samples. Furthermore, the RNA-seq results showed that genes of not only the environmental signaling pathways but also of several insect reproduction-related amino acid metabolic pathways were differentially expressed. Therefore, this implies that the A. corpulenta reproduction was probably regulated by LCP-induced stress.